THE USE OF SLANG WORDS IN THE MOVIE “PITCH PERFECT 3” - JUNIAR .; SYAHRUL EFENDI LUBIS (LP2MTBM MAKARIOZ, 2021)
This research deals with Slang in Pitch Perfect 3 movie. The objectives of this research are to find out the types of slangwords and to describe the reason of using the dominant types of slang in the movie “Pitch Perfect 3”. This research applied adescriptive qualitative method. The data are taken from Pitch Perfect 3 transcript dialogues. Collecting data in this researchis conducted by using documentary technique, because the data in the form of the dialogues in English Text. The result ofthis research shows that not all of Pitch Perfect 3 dialogues contained all types of slang words. Types of slang that are foundin this movie are Abbreviation, Street and Car Term, Baby Expression and Word Repetition. The most dominant type ofslang used in this movie is Abbreviation (49%) and the researcher doesn‟t find any slang words in rhyming slang. Thereasons use the dominant type of slang Abbreviation in this movie are because in order to be brief and concise, also to makethe word simpler and easier to remember both in writing and speaking.